Home Show : 10 Artists' Installations in 10 Santa Barbara Homes. - Ashton, Dore (Santa Barbara : Santa Barbara Contemporary Arts Forum, 1988)
Ericson, Kate ; Ziegler, Mel ; Hamilton, Ann ; Hein, Lisa ; Ireland, David ; Isermann, Jim ; Kosuth, Joseph ; Rothenberg, Erika ; von Rydingsvard, Ursula ; Sato, Norie ; Segalove, Ilene
Home Show : 10 Artists' Installations in 10 Santa Barbara Homes, Santa Barbara Contemporary Arts Forum, Santa Barbara, September 10 - October 9, 1988
boek